The Effect Of Profitability And Liquidity On Firm Value With Dividend Policy As Moderating Variable - Nurmadi, Ruswan; Novietta, Liza (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2022)
The purpose of this research aimed to analyze the effect of Profitability and Liquidity on Firm Value with Dividend Policy as moderating variable. This research used secondary data, which were financial reports from LQ-45 companies that were listed in the Indonesia Stock Exchange (IDX) on the period of 2015-2019. The analysis method used was moderated regression analysis. Based on the results of this research showed that the value of determination after moderation was greater than the value of determination before moderation, which meant that the moderating variable, Dividend Policy (PBV), can strengthen the influence of the Profitability (ROA) and Liquidity (CR) variables on the Firm Value (PBV) variable. Profitability (ROA) had a significant effect on Firm Value (PBV), Liquidity (CR) had a significant effect on Firm Value (PBV), Moderation 1 (DPR) could moderate the effect of Profitability (ROA) on Firm Value (PBV) and Moderation 2 (DPR) cannot moderate the effect of Liquidity (CR) on Firm Value (PBV).